2020
DOI: 10.1200/jco.2020.38.15_suppl.103
|View full text |Cite
|
Sign up to set email alerts
|

NOMINATOR: Feasibility of genomic testing of rare cancers to match cancer to treatment.

Abstract: 103 Background: Rare cancers (RCs) often lack proven treatments and consequently have poorer outcomes. Identification of molecular biomarkers can facilitate treatment selection and trials access for RC patients (pts) where histology-based trials are not feasible. We assessed the potential for next-generation sequencing (NGS) to impact RC care. Methods: Pts with a rare histology, poor-prognosis solid-tumor and no standard of care therapy underwent NGS genomic profiling of paired FFPE tumor and blood (PMCC comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The NOMINATOR study assessed the feasibility of genomic testing in rare cancers [70], also assessing actionability as per the OncoKB annotation [62]. This work optimistically reports 56% of rare tumours with at least one actionable finding.…”
Section: Genomic Alteration In Cupsmentioning
confidence: 99%
“…The NOMINATOR study assessed the feasibility of genomic testing in rare cancers [70], also assessing actionability as per the OncoKB annotation [62]. This work optimistically reports 56% of rare tumours with at least one actionable finding.…”
Section: Genomic Alteration In Cupsmentioning
confidence: 99%
“…1,2 A recent study on rare and advanced tumors revealed that 51% of the tumors analyzed had ≥1 potentially actionable alteration. 3 Nowadays, multimarker tumor panel tests that examine DNA alterations in 200-300 genes are becoming highly used in clinical settings. 4,5 This is due to the growing conviction among clinicians regarding their clinical utility, the development of guidelines recommending their implementation, and the willingness of healthcare payers to provide coverage for the costs associated with these advanced tests.…”
Section: Introductionmentioning
confidence: 99%